Heavy Neutral Leptons and High-Intensity Observables - Abada, Asmaa; Teixeira, Ana M. (Frontiers in Physics, 2018)
New Physics models in which the Standard Model particle content is enlarged via the addition of sterile fermions remain among the most minimal and yet most appealing constructions, particularly since these states are present as building blocks of numerous mechanisms of neutrino mass generation. Should the new sterile states have non-negligible mixings to the active (light) neutrinos, and if they are not excessively heavy, one expects important contributions to numerous high-intensity observables, among them charged lepton flavour violating muon decays and transitions, and lepton electric dipole moments. We briefly review the prospects of these minimal SM extensions to several of the latter observables, considering both simple extensions and complete models of neutrino mass generation. We emphasise the existing synergy between different observables at the Intensity Frontier, which will be crucial in unveiling the new model at work.